Hydrothelphusa vencesi, a new species of freshwater crab (Brachyura: Potamoidea: Potamonautidae) from southeastern Madagascar - Cumberlidge, Neil; Marijnissen, Saskia A.e.; Thompson, Jonelle (Zootaxa, 2007)
A new species of freshwater crab of the genus Hydrothelphusa A Milne-Edwards, 1872, is described based on specimens collected from a forested region of southeastern Madagascar. Hydrothelphusa vencesi n. sp. is clearly distinguished from its congeners by its distinctive first gonopod (G1) with a terminal article that is in the form of a long straight-sided cone, and by a dorsal membrane at the segment junction of G1 that is broad and diamond-shaped. A key is provided to separate the five species of Hydrothelphusa.